2017
DOI: 10.31234/osf.io/kymhp
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How much does education improve intelligence? A meta-analysis

Abstract: Intelligence test scores and educational duration are positively correlated. This correlation can be interpreted in two ways: students with greater propensity for intelligence go on to complete more education, or a longer education increases intelligence. We meta-analysed three categories of quasi-experimental studies of educational effects on intelligence: those estimating education-intelligence associations after controlling for earlier intelligence, those using compulsory schooling policy changes as instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Another question motivated by our results is whether measured environments differentially account for C across age. Finally, environments that do not vary across schools or neighborhoods in the current sample, such as exposure to schooling itself (Gurven et al., ; Ritchie & Tucker‐Drob, ), will not factor into C variation, regardless of their importance for cognitive and academic development.…”
Section: Discussionmentioning
confidence: 98%
“…Another question motivated by our results is whether measured environments differentially account for C across age. Finally, environments that do not vary across schools or neighborhoods in the current sample, such as exposure to schooling itself (Gurven et al., ; Ritchie & Tucker‐Drob, ), will not factor into C variation, regardless of their importance for cognitive and academic development.…”
Section: Discussionmentioning
confidence: 98%
“…Quasiexperimental prospective studies have shown that education improves intelligence. 58 We suspect that since this cohort was ascertained at first admission, the youngest individuals in this cohort experienced more educational disruption. It is possible in individuals with psychotic disorders, the advantage provided by the Flynn effect is counteracted by educational disruptions.…”
Section: Limitationsmentioning
confidence: 99%
“…Schooling, with its primary function of academic instruction, can explain bidirectional relations between cognitive abilities and academic performance (Ceci & Williams, ; Jacob & Parkinson, ; Ritchie & Tucker‐Drob, ). Early on, children use cognitive abilities to learn academic skills, and performing most academic tasks involves the use of those cognitive abilities (Evans & Stanovich, ; Peng et al, ).…”
Section: Mechanisms Of Cognitive‐academic Bidirectionalitymentioning
confidence: 99%